Geoheritage Values of the Northeastern Carpathians, Transcarpathia, Ukraine - Sandor Gonczy; Gyula Fodor; Natalia Olah; Tibor Nagy; Zsuzsanna Ésik; János Szepesi (Geoconservation Research)
Transcarpathia politically is the westernmost county of Ukraine but geographically is the north–eastern part of the Carpathian–Pannonian Region. The aim of our present work is to provide a brief overview and greater publicity about the geoheritage values of Transcarpathia using 45 documented geosites (stratigraphic, volcanic, geomorphological, mineralogical, tectonic) of the Ukrainian State Geological Survey. Four objects are located in national parks or nature reserves. The other 41 sites are only recommended for protection. The applied classification scheme included thematic (primary and additional interest) and functional categories (e.g. natural outcrops, quarries). The preliminary qualitative site assessment involved the determination of integrity, geological diversity, use limitations, current observation conditions, vulnerability, safety, association with other values parameters. This review is a good methodological starting point for expanding the database and emphasizing the importance of the abiotic nature. Conserving geodiversity requires protection for nationally or regionally important objects what includes active management of sites.